THE IMPORTANCE OF SCHOOL PHYSICAL EDUCATION IN THE DEVELOPMENT OF MOTOR GESTURES IN ELEMENTARY SCHOOL CHILDREN. (Fiep Bulletin - online, 2024)
Considering the paper of the physical education in the school extent that and the one-off forming the lucid and committed human being with his/her social reality and with a better life quality, this comes to provide through one practice conscious, an including development capable to associate partner-affectionate and motor values. Like this in that way the motor development had allowed the individual to have more complex and specific motive actions and it is in that context that the teacher of Physical Education will be the link that will tie the student, the school and the society. Based in this reality this study verified a significant difference in the students of the net of private teaching motive age compared to the of the public net of teaching. Because when being verified more select movements as the motricities fine, global and the balance, the students of the private net of teaching demonstrated a significant difference in the movements; this is due the most specific opportunities of development that they have, showing and affirming the paper of the physical education in the school extent and the physical education professional's commitment based scientifically in the student's development during the acquisition of motive abilities and the establishment of goals. Already the students of the public net of teaching cannot enjoy this powerful artifice in what refers to the motor development and the physical education classes.
Keywords: Physical Education Scholl – Development Motor - Tests of Functions Psicomotriz - Fundamental Teaching.